Hyperspectral imaging, mineralogy, and degassing: Exploring the volcanic hydrothermal system of Red Crater, Tongariro, Aotearoa New Zealand - Sturgess D; Kereszturi G; Mazot A; Sanchez R; Álvarez-Valero AM; Zakharovskyi V (Elsevier BV, 2026)
Hydrothermal alteration on volcanoes can compromise the strength and permeability of the host rock, contributing to flank collapses (e.g., Te Maari, 2012) and phreatic eruptions (e.g., Whakaari, 2019). Alteration processes occur at volcanoes hosting hydrothermal systems, where hot, acidic fluid flow is driven by a supply of magmatic heat and gas inputs, resulting in the dissolution of primary minerals and the deposition of secondary assemblages. We investigated hydrothermal alteration at Red Crater, Tongariro, Aotearoa New Zealand, using a combination of laboratory and airborne hyperspectral imaging, mineralogical, and geochemical techniques. Two distinct alteration styles were identified: (1) advanced argillic alteration, characterised by amorphous silica, kaolinite, and alunite, primarily focused at the Red Crater scoria cone, and (2) silicification at Oturere and the Emerald Lakes. The distribution of these units was mapped using supervised image classification of airborne hyperspectral data. Textural and isotopic analyses suggest acid-sulphate alteration is primarily driven by the oxidation of rising H2S in a steam-heated environment. Red Crater hosts four main regions of heightened degassing, coinciding with geothermal surface features and hydrothermal alteration deposits, with 26.2 +- 1.5 t/d of CO2 emissions and an H2S flux of 131.1 g/m2/d. This study presents a conceptual model of hydrothermal alteration processes at Red Crater. Our mapping of alteration and degassing can indicate areas of potential future hazards, and may support simulations assessing flank instability, improving hazard assessment at this active vent.
Keywords: Hyperspectral imaging; Imaging spectroscopy; Hydrothermal alteration; Volcano mapping; Degassing; Geochemistry